The Washington manual allergy, asthma, and immunology subspecialty consult - Kau, Andrew L.; Monroy, Jennifer M.; Polk, Brooke I.; Rigell, Christopher J.; Ciesielski, Thomas (Washington manual subspecialty consult series., 2022)
"Prepared by specialty residents, fellows and staff in the Department of Medicine at Washington University School of Medicine, and reviewed by attending physicians in each field-each volume in this renowned series delivers the on-thespot help you need to provide quality patient management. Right from the initial chapter, you'll learn how to take a patient history, how to interpret exam findings, what tests to order, how to complete the workup, and how to formulate an effective management plan. The Third Edition of this dynamic quick reference continues to provide the practical, stepwise guidance you've come to trust from The Washington Manual and has been fully updated to include the most current diagnostic tests, workup tips, drugs and other therapeutic interventions available"--